The status of Arctic charr, Salvelinus alpinus (L), in southern Scotland: a cause for concern - Peter S. Maitland (Freshwater Biological Assoication, 2010)
In the British Isles, the Arctic charr (Morton 1955), Salvelinus alpinus (L.)(see Fig. 1), in individual lakes have been isolated from each other forthousands of years and have developed a variety of phenotypiccharacteristics (Gunther 1865; Day 1887; Regan 1909, 1914) which areprobably genetically based (Nyman 1972; Child 1977, 1984; Ferguson1981). The differences between some populations are so great that manywere originally described as distinct species.